Utilization of Immunoblotting in Studies of Epitope Targeting in Monoclonal Antibodies to Melioidosis Agent Antigen 200 kDa - I. I. Korsakova; N. P. Khrapova; T. V. Zamarina; E. V. Pimenova; N. S. Makarov; Yu. A. Goloseev (Проблемы особо опасных инфекций, 2014)
Objective of the research was to use immunoblotting for studies of epitope targeting in monoclonal antibodies to 200 kDa Burkholderia pseudomallei antigen, which are synthesized by hybridomas-producers from the two collections in the laboratory of immunodiagnostics and biotechnology at the premises of Volgograd Research Anti-Plague Institute. Employed were 8 typical strains of melioidosis agent with the complete antigenic structure. Antigen preparations were separated by means of denaturating vertical electrophoresis in 12 % polyacrylamide gel with 0.1 % sodium dodecylsulfate. During the process of cell-replication, 12 hybridomas-producers were given preparative amounts of monoclonal antibodies to 200 kDa Burkholderia pseudomallei glycoprotein. Following that, immunoperoxidase conjugates were manufactured. Epitope targeting of monoclonal antibodies was evaluated using immunoblotting. With the help of vertical electrophoresis identified was the presence of several mandatory major components contained in the antigen complexes of the salt-water and formamid B. pseudomallei extracts . Differential staining substantiated glycoprotein origin of certain antigen components. Immunoblotting with the stated above antigen preparations revealed epitope targeting of a number of monoclonal antibodies to 200 kDa antigen of melioidosis agent; demonstrated were the differences in their specific interaction with biopolymers which form part of the antigen specter. Those differences were characteristic of hybridomas-producers belonging to different collections, as well as of particular strains of B. pseudomallei.